Optimalisasi Pengelolaan Sampah dalam Perspektif Pendidikan Islam Di Perumahan Kelurahan Tamansari Kecamatan Bondowoso - Iro Waziroh (Fakultas Agama Islam, 2017)
Waste is one of the problems that can not be avoided by the population. Increasing population causes increased activity of the population, which means also can increase the amount of waste, it is due to the many sources of waste that have sprung up such as in housing, tourist attractions, and other public facilities, which can cause increased waste in housing tamansari village bondowoso district, a waste management system that is available is still limited and they rely on empty land disposal of waste and TPS there is still not good and the condition lug garbage in housing tamansari village bondowoso district still mixed or without sorting, so that people who throw their garbage has not been able to do the sorting for a variety of organic and inorganic waste. So in the housing tamansari village bondowoso district requires efforts to optimize the process of waste management in the review based on the generation and waste characteristics and land conditions, So these problems to do an analysis condition of waste management in housing tamansari village bondowoso district, then get the facilities and infrastructure needs is not good enough, so it appears the problem of garbage in the location is still a lack of research and polling services lug garbage in each source. Based conditions, people still follow the custom of throwing garbage in the river and dispose of their garbage in vacant land. Thus the need in optimizing waste management in housing tamansari village bondowoso district, with the addition of lug and waste collection system in accordance with the state of the location, so that the lug and garbage collection system to be effective. And sticking ti the qur’an and hadis about cleanliness is part of faith